ASSOCIATION BETWEEN CARDIAC (PRO)RENIN RECEPTOR EXPRESSION AND MYOCARDIAL HYPERTROPHY IN HUMAN. (April 2021) - Morimoto, Satoshi; Morishima, Noriko; Watanabe, Daisuke; Kato, Yoichiro; Sawada, Tatsuo; Shibata, Noriyuki; Ichihara, Atsuhiro
Abstract : Objective: The (pro)renin receptor [(P)RR] is expressed in vital organs throughout the body, with the highest expression level in the heart, and is thought to regulate the tissue renin-angiotensin system (RAS) through the non-proteolytic activation of prorenin. (P)RR is cleaved by processing enzymes to generate soluble (s)(P)RR, which is secreted into the extracellular space, and blood concentration of s(P)RR is considered to reflect the expression level of tissue RAS. Although it has been suggested that increased expression of (P)RR may be involved in cardiac pathophysiology in experimental studies, the significance of (P)RR expression in human heart remains unclear. Therefore, in the present studies, we investigated association between cardiac (P)RR expression and myocardial hypertrophy in human. Design and method: Study (1): We measured serum s(P)RR concentration and assessed the relationships between serum s(P)RR level and background factors including left ventricular mass index (LVMI) in 135 patients (57 males) of our department. Study (2): We performed immunostaining for (P)RR and atrial natriuretic peptide (ANP) and α-skeletal actin (SKA), markers for myocardial hypertrophy, in left ventricle specimens obtained from 13 autopsy cases. The expression level of (P)RR, ANP, or SKA and cardiomyocyte area were analyzed using an image processing software (ImageJ) and expression level of (P)RR was compared with cardiomyocyte area and expression level of ANP or SKA. Results: Study (1): The patients' age was 57 (44–67) y.o., serum s(P)RR concentration was 22.8 (21.1–27.7) ng/ml, eGFR was 74.4 (59.4–91.2) ml/min/1.73 m 2, and LVMI was 79 (66–90) g/ m 2 . Serum s(P)RR level was significantly positively correlated with LVMI (β = 0.238, p < 0.01) independent of other related factors. Study (2): (P)RR immunostaining was observed in cytoplasm of cardiomyocytes. The expression level of (P)RR was significantly positively correlated with cardiomyocyte area (ρ = 0.386, p < 0.001) and expression level of ANP (ρ = 0.782, p < 0.001) or SKA (ρ = 0.373, p < 0.001). Conclusions: These data suggested that cardiac (P)RR expression may be associated with myocardial hypertrophy in human. Further studies are needed to determine the underlying mechanism of this association.